AN INTERNATIONAL TREATY ACCORDING TO THE CONVENTION OF VIENNA 1969 AND CORRELATION WITH INTERNATIONAL TRADING COOPERATION IN INDONESIA - Magdariza Magdariza (LPPM Universitas Ekasakti Padang, 2023)
The international cooperation is an important in interstate relation aspect. It is required an international agreement. The agreement in international law was established in Convention of Vienna 1969. The Convention 1969 is the regulation of internal law was agreed by the states including Indonesia. Even though have not ratifying yet the Convention of Vienna 1969, however, Indonesia persists oblige to the custom of international law. The national law of Indonesia is regulating how to implement the international agreement. It is described on Act No.24 of 2000 on International Agreement. Ironically, however, the regulation of international trading cooperation of the Act No.7 of 2014 contravene to the provision as was agreed by all the state, i.e. Convention of Vienna of 1969. One of article is No.85 the Act No.7 of 014. The national law of Indonesia has contravened the “pactasuntservanda”principle.Moreover, there is an inappropriate provision to the national law of Indonesia. There is must be a modification of international law in correlation of international trading.